2017
DOI: 10.3892/ol.2017.6159
|View full text |Cite|
|
Sign up to set email alerts
|

Isoliquiritigenin induces apoptosis of human bladder cancer T24 cells via a cyclin-dependent kinase-independent mechanism

Abstract: The aim of the present study was to investigate whether an increase in cyclin-dependent kinase 2 (CDK2) activity is involved in apoptosis of human bladder cancer T24 cells induced by isoliquiritigenin (ISL). The viability of T24 cells was estimated using a sulforhodamine B assay. Cell morphological changes were examined using Hoechst 33258 staining. The apoptotic rate was determined by staining cells with Annexin V-fluorescein isothiocyanate and propidium iodide labeling. The mitochondrial membrane potential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…Flavonoids have received significant attention in this regard, not only as preventative strategies, but also as potential chemotherapeutic agents [16,17]. In particular, isoliquiritigenin (ISLQ), a chalcone-derived flavonoid naturally found in liquorice and shallots [18], has been investigated for its anticancer properties due to its potent inhibition of cell proliferation and viability in a range of cancer cell types [19][20][21][22][23][24][25][26][27][28][29]. The anticancer effects of ISLQ on NB are yet to be studied, however ISLQ has recently been found to induce cytotoxicity in the pheochromocytoma (PC-12) cell line, which, like NB, has a neural crest origin [30], suggesting that ISLQ may have anticancer effects in NB cells.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids have received significant attention in this regard, not only as preventative strategies, but also as potential chemotherapeutic agents [16,17]. In particular, isoliquiritigenin (ISLQ), a chalcone-derived flavonoid naturally found in liquorice and shallots [18], has been investigated for its anticancer properties due to its potent inhibition of cell proliferation and viability in a range of cancer cell types [19][20][21][22][23][24][25][26][27][28][29]. The anticancer effects of ISLQ on NB are yet to be studied, however ISLQ has recently been found to induce cytotoxicity in the pheochromocytoma (PC-12) cell line, which, like NB, has a neural crest origin [30], suggesting that ISLQ may have anticancer effects in NB cells.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that ISL suppressed osteosarcoma cell proliferation in a time-and dose-dependent manner. Additionally, 20 μM ISL significantly inhibited cell growth at 72 h. Si et al [20] had also observed that cell proliferation decreased in human bladder cancer T24 cells after treatment with ISL. The inhibi- tory influence of ISL on cell migration or invasion has been described in melanoma cells [21], prostate cancer cells, and breast cancer cells [22,23].…”
Section: Discussionmentioning
confidence: 92%
“…ISL-induced apoptosis has been observed in bladder cancer T24 cells, human lung cancer cells, and endometrial cancer cells [18,20,27]. Si et al [20] found that ISL induced apoptosis in bladder cancer T24 cells by enhancing the protein expression level of Bax and Caspase-3 and decreasing the level of antiapoptotic protein Bcl-2. Moreover, Wu et al [18] reported that ISL markedly induced apoptosis by upregulating the cleavage of Caspase-3 and -7 and PARP expression in endometrial cancer, Ishikawa, or HEC-1A cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations